(untitled) (Bangladesh Journal of Botany, 2008)
Seven components have been identified including caryophyllene oxide (24.14%), caryophyllene (22.19%), limonene (21.79%) and myrcene (9.02%), as significantly dominating compounds of essential oil from inflorescences of Spilanthes calva DC. from Bangladesh investigated by gas chromatography mass spectrometry. Key words: Spilanthes calva, Essential oil, GC-MS, Caryophyllene oxide doi:10.3329/bjb.v37i2.1737 Bangladesh J. Bot. 37(2): 217-218, 2008 (December)